Ahmad Dahlan dan Pergerakan Muhammadiyah: Idea-idea Pembaharuan dalam Konteks Kebudayaan dan Sejarah - nabil amir, ahmad (Fakultas Studi Islam Universitas Muhammadiyah Riau, 2025)
The paper aims to analyze the influence of Kiyai Haji Ahmad Dahlan (1868-1923) in inaugurating Islamic modernism in Indonesia by investigating his role and involvement in Muhammadiyah. The modern reform movement was inspired by profound moral and religious factors and its puritanical cause leading to the formation of Muhammadiyah in 18 November 1912. The objective of study is to reveal the underlying philosophy and framework that inspired the religious struggle of Muhammadiyah and the pioneering role of Ahmad Dahlan in organizing its modern ideal and social spirit. The study is based on qualitative framework in the form of literature survey that analyze technical and scientific data using empirical, descriptive and historical approaches. The finding shows that Ahmad Dahlan had bring decisive impact on Islamic modernism by bringing into perspective the tawhidic and puritanical aspect of Muhammadiyah that projected its modern and ethical tradition and consciousness. Its rising influence in modern context was driven by an extensive network of Muhammadiyah’s activist and missionaries that help to realize its dakwah aspiration that emphasized on moral and intellectual development and its meaningful and practical impact on society. It highlighted the social aspect that drive the cosmopolitan vision of Muhammadiyah and the strength of its organization, widely held as the largest and most organized and systematic Islamic movement in the world.